A comparison study between electrospun polycaprolactone and piezoelectric poly(3-hydroxybutyrate-co-3-hydroxyvalerate) scaffolds for bone tissue engineering; Colloids and Surfaces B: Biointerfaces; Vol. 157 - Gorodzha S. N. Svetlana Nikolaevna; Muslimov A. R. Albert Radikovich; Syromotina D. S. Dina Sergeevna; Timin A. S. Aleksandr Sergeevich; Tsvetkov N. Yu. Nikolay Yurjevich; Lepik K. V. Kirill Viktorovich; Petrova A. V. Aleksandra Vladilenovna; Surmeneva M. A. Maria Alexandrovna; Gorin D. A. Dmitry Aleksandrovich; Sukhorukov G. B. Gleb Borisovich; Surmenev R. A. Roman Anatolievich (2017, 2017)
Title screen